2018
DOI: 10.1021/acsomega.8b00763
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Nanosized Disordered LiVOPO4

Abstract: ε-LiVOPO 4 is a promising multielectron cathode material for Li-ion batteries that can accommodate two electrons per vanadium, leading to higher energy densities. However, poor electronic conductivity and low lithium ion diffusivity currently result in low rate capability and poor cycle life. To enhance the electrochemical performance of ε-LiVOPO 4 , in this work, we optimized its solid-state synthesis route using in situ synchrotron X-ray diffraction and applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 74 publications
2
36
0
Order By: Relevance
“…[ 10a ] It should be noticed that both Bianchini's and Lin's works used LiVOPO 4 synthesized by solid‐state method and subjected to high‐energy ball‐milling to reduce particle size, which introduces structural disorder as will be discussed later. [ 20 ] Wangoh et al., using a combination of hard and soft X‐ray photoelectron and absorption spectroscopy techniques, have shown that uniform Li distribution in ε‐LiVOPO 4 is a prerequisite to the formation of Li 1.5 and Li 1.75 VOPO 4 phases. Also, it ensures uniform second Li intercalation to form the Li 2 VOPO 4 .…”
Section: Metastable Structures Of Lixvopo4 (X = 15 175 2) Phases:mentioning
confidence: 99%
See 4 more Smart Citations
“…[ 10a ] It should be noticed that both Bianchini's and Lin's works used LiVOPO 4 synthesized by solid‐state method and subjected to high‐energy ball‐milling to reduce particle size, which introduces structural disorder as will be discussed later. [ 20 ] Wangoh et al., using a combination of hard and soft X‐ray photoelectron and absorption spectroscopy techniques, have shown that uniform Li distribution in ε‐LiVOPO 4 is a prerequisite to the formation of Li 1.5 and Li 1.75 VOPO 4 phases. Also, it ensures uniform second Li intercalation to form the Li 2 VOPO 4 .…”
Section: Metastable Structures Of Lixvopo4 (X = 15 175 2) Phases:mentioning
confidence: 99%
“…There are several methods for synthesizing LiVOPO 4 , the most commonly used ones being the solvothermal (ST), [ 7b,18c,31 ] sol–gel (SG), [ 18b,26,32 ] solid‐state (SS) [ 10a,19,20,30,33 ] methods, or by using a (Li)VOPO 4 ⋅2H 2 O precursor. [ 7a,17,34 ] We placed general information on advantages of each of these approaches in the Supporting Information, and will focus here on the application of these methods to LiVOPO 4 synthesis.…”
Section: Synthesis and Its Impact On The Electrochemical Performance mentioning
confidence: 99%
See 3 more Smart Citations